Tumor budding in colorectal adenocarcinoma using cytokeratin 20 immunostaining - Chaitra N; Sundar RNS; Kumar HKS; Nataraju G; Esaivani KB (Journal of Medical and Scientific Research, 2023)
Introduction: Colorectal cancer is the third most common cancer worldwide and second most common fatal cancer. Tumor budding is an emerging prognostic indicator in cancers. Though tumor budding can be assessed using Hematoxylin and Eosin stain, sometimes peritumoral inflammation and reactive stromal fibrosis obscures the tumor buds. The present study aimed to assess tumor budding using cytokeratin 20 immunohistochemistry in colorectal cancers.